Loose Parts Media in Islamic Religious Education Learning at Mutiara Ibu Elementary - Sudadi; Umi Zulfa; Sutarman; Parjiman; Rose Kusumaningratri; Antoni; Siti Munawaroh (Bulletin of Pedagogical Research, 2025)
Loose parts are materials that can be moved, combined, separated, and reassembled in various ways. Loose parts can be natural or synthetic materials that are used creatively and flexibly to support learning. This study aims to determine the effectiveness of using loose parts media in Islamic Religious Education (PAI) learning at SD Mutiara Ibu Purworejo. This study uses a descriptive qualitative method with data collection techniques through observation and documentation during PAI learning activities. The results of the study indicate that the use of loose parts media can increase creativity, active participation, and students' understanding of PAI materials. With this media, students are more enthusiastic in learning PAI without feeling bored. In addition, there are challenges faced by teachers, namely in terms of selecting materials that are in accordance with the material and managing learning activities. However, with good planning, loose parts media can finally become an effective innovation to improve the quality of PAI learning at SD Mutiara Ibu.